InGaN-based green micro-LED efficiency enhancement by hydrogen passivation of the p-GaN sidewall. (1st August 2022) - Kirilenko, Pavel; Iida, Daisuke; Zhuang, Zhe; Ohkawa, Kazuhiro
Abstract: We investigated the effect of the sidewall passivation by hydrogen plasma on the InGaN green micro-LED performance. Hydrogen passivation deactivates the surface region of p-GaN around the perimeter of the device mesa. Thus, hole injection is suppressed in this region, where etching-caused material degradation results in leakage current, decreasing device efficiency. We have confirmed the hydrogen passivation effect on LED square pixels with sizes of 20 and 100 μ m. For smaller LEDs, the reverse leakage current has reduced more than tenfold, and the external quantum efficiency of LEDs was enhanced 1.4-times due to the suppression of the non-radiative recombination.